2020
DOI: 10.1186/s13063-020-4126-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular exercise and pain neuroscience education compared with pain neuroscience education alone in patients with chronic pain after primary total knee arthroplasty: study protocol for the NEPNEP randomized controlled trial

Abstract: Background: Total knee arthroplasty (TKA) is considered an effective treatment for pain relief and improved physical performances in end-stage knee osteoarthritis. However, several studies have reported less favorable outcomes after TKA with chronic pain rates of approximately 20%. Exercise might be an effective treatment strategy for chronic pain following TKA, but no randomized controlled trials have evaluated its effect. Therefore, the purpose of this randomized controlled trial is to investigate whether a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…It has been shown that neuroscience education is effective in improving muscle strength. In this study, PNE increased the patients' interest in functional activity and exercise and motivated them to perform more frequent and intense activities, thereby improving physical ability and reducing pain [47]. In addition, PNE has been reported to have a positive effect of changing incorrect pain beliefs and incorrect movements of the lower back [23], thus allowing patients to more actively participate in the LSE program without fear of exercise.…”
Section: Discussionmentioning
confidence: 80%
“…It has been shown that neuroscience education is effective in improving muscle strength. In this study, PNE increased the patients' interest in functional activity and exercise and motivated them to perform more frequent and intense activities, thereby improving physical ability and reducing pain [47]. In addition, PNE has been reported to have a positive effect of changing incorrect pain beliefs and incorrect movements of the lower back [23], thus allowing patients to more actively participate in the LSE program without fear of exercise.…”
Section: Discussionmentioning
confidence: 80%
“…Ginn et al [25] demonstrated that exercises to restore neuromuscular control were as effective as corticosteroid injections in treating shoulder pain in the short term. In addition to the shoulder, NME has a significant therapeutic effect on many other musculoskeletal pain conditions, such as low back pain [39,40], neck pain [41], chronic musculoskeletal pain in the elderly [42], chronic pain after primary total knee arthroplasty [43], and knee and hip osteoarthritis [44,45]. NME includes active exercises of strength, coordination, balance, and proprioception.…”
Section: Evaluation Of the Effect Of Neuromuscular Exercise On Painmentioning
confidence: 99%
“…The compound and development of the pain neuroscience education intervention were based on previous studies [17,[38][39][40]. Pain neuroscience education discussed peripheral sensitization, central sensitization, and biopsychosocial factors associated with pain [19,41].…”
Section: Pain Neuroscience Educationmentioning
confidence: 99%
“…The sessions covered topics concerning the multifactorial nature of chronic pain, sensitization, and plasticity of the brain, aiming at giving patients a better understanding of their chronic pain and thereby engaging the patients in the treatment. [39]. Patients were also taught items such as the physiology of the synapse, the neuron (receptor, axon, and terminal), descending nociceptive inhibition and facilitation (the influence of cognitive factors, notion, motor activities, etc.…”
Section: Pain Neuroscience Educationmentioning
confidence: 99%